Demulsification of oily wastewater using a nano carbon black modified with polyethyleneimine. (May 2022) - Chen, Lihan; Ye, Fan; Liu, Hanjun; Jiang, Xuebin; Zhao, Qingmei; Ai, Guosheng; Shen, Liwei; Feng, Xuening; Yang, Ying; Mi, Yuanzhu
Abstract: In this work, nano carbon black was modified with polyethyleneimine (CB-PEI) under an ultrasonic field. The obtained product was used as a demulsifier to break oily wastewater. Morphology, structure, and chemical composition of CB-PEI were systematically analyzed. Bottle test was carried out to evaluate the influence of dosage, pH value and salinity on the demulsification efficiency of the emulsion. The results showed that the light transmittance of water phase (TSW) after the demulsification was 79.1% and corresponding oil removal rate (ORR) could reach up to 99.4% with 60 mg/L of CB-PEI at ambient temperature for 30 min. In addition, the possible demulsification mechanism was explored by dynamic interface tension (IFT), elasticity modulus, wettability, self-assemble of interfacial membrane, zeta potential and micrograph analysis. It indicated that CB-PEI had an appropriate amphiphilicity and good interfacial activity, which could improve it quickly transfer to the oil-water interface and result in the oil-water separation. The current work provides a simple method to prepare a demulsifier with excellent performance, so it has a good application prospect for the treatment of oil-water emulsions. Graphical abstract: Image 1 Highlights: CB-PEI with amphipathy and interfacial activity is prepared via ultrasonication. CB-PEI can be widely used at high salinity and wide pH range. Synergistic effect of π-π interaction and electrostatic attraction induces the demulsification. An ultra-low dosage of CB-PEI is utilized to break oily wastewater.